PENGARUH POLUSI UDARA TERHADAP KESEHATAN PARU-PARU PADA ANAK-ANAK DI KAWASAN INDUSTRI KOTA MEDAN - ALEXANDER PARLINDUNGAN MARPAUNG (LP2MTBM MAKARIOZ, 2023)
Medan is one of the cities that has an industrial area located in the mabar area of Medan Deli District, where this area has several medium and large-scale industries, where there are some akryawan who choose to live in the area, but there are also houses of non-employees who still exist around the industrial area. The obstacle is the increase in noise pollution and air pollution that pollutes the environment of residents who make residents, especially some children living in the area experience lung pain (pneumonia), where this illness is caused by inhalation of smoke or pollutants from factory chimneys. This study aims to find out some of the problems that make the situation that occurs in industrial estates cannot be prevented because companies need to dispose of pollutants through factory chimneys, then how are the ways done by industrial estates and the government in overcoming the problem of the outbreak of lung disease for children living around the area. This research was conducted using qualitative descriptive analysis. The results of the study explain the things that have been done by the industrial estate in preventing the increase of lung disease in children in industrial insights in Medan, among others, by implementing a carbon emission control system, determining environmental hygiene standards in industrial estate areas, collaborating with the Government to implement green open areas to prevent pollution, and conducting counseling and coaching to the community to be aware of the rampant disease lungs by children who are in industrial areas, while the things that must be done by the government to prevent lung disease in children living in the Medan Industrial area are by implementing counseling and counseling on lung diseases, supervising the implementation of environmental standards in industrial insights, building systems to monitor air quality in industrial insights, collaborating with industrial insights to build green open areas, improving medical services, implement a system that reduces the social impact of industrial activity in residential areas